Religions in Context: The Response of Non-Mormon Faiths in Utah - Stark, Rodney (Review of religious research, 2004)
Utah provides a rare opportunity to see how minority religious bodies respond when faced, not with a lazy "monopoly" faith, but one that is energetic and effective. Based on our theoretical work, we predict that faced with Mormon competition, even liberal Protestant bodies will display far higher levels of commitment in Utah than elsewhere in the nation. The data agree.